Bioguided Phytochemical Study of Ipomoea cairica Extracts with Larvicidal Activity against Aedes aegypti - Álvarez Valverde, Víctor (2022)
Vector-borne diseases, such as those transmitted by Aedes aegypti, are a constant threat to inhabitants of tropical regions of the planet. Synthetic chemicals are commonly used as a strategy to control them; however, these products are known to persist in ecosystems and drive the appearance of resistance genes in arthropod vectors. Thus, the use of natural products has emerged as an environmentally friendly alternative in integrated vector control strategies. The present bioguided study investigated the larvicidal potential of Ipomoea cairica extracts, fractionated using thin-layer and open-column chromatography, because this species has been shown to exert larvicidal effects on the genus Aedes. The objective of this study was to evaluate the nonvolatile components in ethanolic extract of I. cairica stems as a potential natural larvicidal, and coumarins, such as 7-hydroxy- 6-methoxychromen-2-one (scopoletin) and 7-hydroxychromen-2-one (umbelliferone), were identified as major compounds; however, they were not shown to be responsible for the larvicidal activity. Based on the results of the larvicidal action tests, these coumarins are not directly responsible for the larvicidal activity, but this activity might be attributed to a synergistic effect of all the compounds present in the most active secondary fraction, called F.DCM, which had an LC50 value of 30.608 mg/L. This type of study has yet not been conducted in the region; therefore, it is an important contribution to recognizing a natural and easy-to-cultivate source of vector control, such I. cairica.